DATA GENERATION FOR THE ACQUISITION OF THE UNIVERSITY COURSES OF INFORMATICS AND STATISTICS IN THE HEALTH CARE SPECIALITIES - Rasnacs, Oskars; Vitins, Maris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The authors of the present article are investigating the influence of the data generation in the university courses of informatics and statistics (UCIS) on the acquisition of both the UCIS and other study courses in the health care specialities. First of all, the authors inquired students in order to find out their attitude to the UCIS. The inquiry results show evidence that an important role in the acquisition of UCIS has the work/study material – data. The UCIS work/study material can be associated with various branches, including health care. The data of the health care patients are of a special status. Their use is strictly regulated/limited.by legislation. The authors of the present article offer an acceptable solution – data associated with the health care patients are generated from the parameters of statistics of scientific publications. Investigations were performed in the Red Cross Medical College of Rīga Stradiņš University (RCMC of RSU). It was found out that the data generation resulted in higher marks both in UCIS and many other study courses. In this article, the authors present proposals how to generate data comparatively easy, apply traditional MS Excel generation tools as well as tools of Goal Seek and Solver.